Analisis Landasan Ilmu Pengetahuan dan Teknologi Pendidikan dalam Pengembangan Multimedia Interaktif - Ariani, Rizka; Festiyed, Festiyed (Universitas Negeri Padang, 2019)
Research conducted includes descriptive research. On descriptive statistics without analyzing and making conclusions that apply to the public. The population in this study are articles and online books analyzed. The samples in this study are some of the articles analyzed, taken according to the topic. Educational institutions, especially school path education, must be able to accommodate and anticipate the development of science and technology. Teaching material should be the result of the development of the latest science and technology, both related to the results of information acquisition, as well as how to obtain that information and utilize it for the community. With the advancement in technology, it is possible to produce interactive learning media that are interesting and fun for teaching and learning. As Suheri (2006) argues that multimedia gives a pleasant impression of helping the learning process in remembering and multimedia learning in the classroom is not a new phenomenon, but advances in computer technology enable multimedia to be developed to present learning material interactively